Enhancing local governance in Nepal through federalism: A study of key elements - Adhikari, Hari Prasad (Journal of Nepalese Management Academia, 2023)
Federalism and local governance are mutually inclusive and complementary at times but they are different concepts. It involves multiple aspects such as national, political, legislative, institutional, and fiscal dimensions. Federal processes have the potential to influence and shape local governance. The purpose of this study is to investigate the elements of federalism that can improve local governance in Nepal. A descriptive and analytical research design was employed to collect data from 384 respondents via a questionnaire for analysis. While the elements of federalism for enhancing local governance were found to be satisfactory, the study highlights the inadequacies in its implementation. The findings provide valuable insights into Nepal’s federalism policy and offer guidelines to policymakers for improving local governance. Additionally, the study emphasizes the need for appropriate policies, robust communication, and information systems to support the federalism process from the federal government.